EVALUASI PENAMBAHAN BAKTERI NITROSOMONAS TERHADAP KUALITAS AIR IKAN LELE (Clarias sp.) - Lintang Hadi; Muhammad Marzuki; Fariq Azhar (Universitas Sriwijaya, 2022)
Catfish is one of the aquaculture products which ranks at the top in the amount of freshwater aquaculture production produced. So far, catfish has contributed more than 10% of national aquaculture production with a growth rate of 17 to 18%. The Ministry of Maritime Affairs and Fisheries targets aquaculture production to reach 22.46 million tons in 2017. Catfish is one of the aquaculture products that ranks at the top in the amount of freshwater aquaculture production produced. Heterotrophic bacteria can be needed as organisms to decompose feed residues or organic matter present on the bottom of the water. The provision of heterotrophic bacteria is expected to reduce ammonia and nitrite levels in catfish culture. This study aims to determine the effectiveness of the administration of Nitrosomonas bacteria on the water quality of catfish (Clarias sp.). The results of this study indicate that the addition of Nitrosomonas bacteria can affect growth, feed conversion, survival rates and water quality. This study used an experimental method with a completely randomized design with 4 (four) types of treatment and 3 (three) replications. The results of the addition of Nitrosomonas bacteria as much as 2% of the total volume of water (P4) gave the best effect on the growth and survival of catfish (Clarias sp.) with a specific growth value of 5.00%, a survival value of 76.67% and a conversion value feed is 1.96, while the lowest ammonia value is 0.35 mg/L.